Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/c9ra08047c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling provides a structural basis for PERK inhibitor selectivity towards RIPK1

Abstract: Molecular modelling explains the lack of selectivity for inhibitors GSK2606414 and GSK2656157, as compared to inhibitor AMG44.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…et al For GSK'157 suggested a good selectivity profile of the compound, even though RIPK1 was not included in the panel. In this study we confirmed the hypothesis that the potency and selectivity for RIPK1 could be increased by derivatising the corresponding para-position of the GSK'157 pyridinyl ring (Axten et al, 2013;Chintha et al, 2019). In addition, based on the mode of interaction of While for the latter the binding site is slightly solvent-exposed, for RIPK1 the pocket is buried, featuring a more hydrophobic profile due to the presence of three Leu, two Val, and Met (not shown in detail).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…et al For GSK'157 suggested a good selectivity profile of the compound, even though RIPK1 was not included in the panel. In this study we confirmed the hypothesis that the potency and selectivity for RIPK1 could be increased by derivatising the corresponding para-position of the GSK'157 pyridinyl ring (Axten et al, 2013;Chintha et al, 2019). In addition, based on the mode of interaction of While for the latter the binding site is slightly solvent-exposed, for RIPK1 the pocket is buried, featuring a more hydrophobic profile due to the presence of three Leu, two Val, and Met (not shown in detail).…”
Section: Discussionsupporting
confidence: 82%
“…The reported structure-activity relationship (SAR) suggested that derivatisation of the corresponding para-position of the pyridinyl ring could reduce affinity for PERK (Axten et al, 2012;. Moreover, recent molecular modelling studies confirmed the different nature of the C-alpha helix domain in RIPK1 with the presence of an additional lipophilic pocket compared to PERK (Chintha et al, 2019). We investigated the structural differences between PERK and RIPK1 and we verified the presence of an extra pocket with additional space to place the para-substituent.…”
Section: Introductionmentioning
confidence: 76%
“…We then asked which one or a combination of the three ER stress-responding pathways ( Ron and Walter, 2007 ) were involved in Alternol treatment-induced ER stress. We utilized pathway-selective pharmacological inhibitors for these three pathways, IRE1α inhibitor MKC8866 ( Sheng et al, 2019 ), PERK inhibitor AMG44 ( Chintha et al, 2019 ), and ATF6 inhibitor CEAPIN-A7 ( Xue et al, 2021 ) to determine their involvement in Alternol-induced ER stress response ( Figure 3D ). Our results showed that pretreatment with AMG44 reduced the Alternol-induced ATF4 expression while MKC8866 pretreatment suppressed Alternol-induced XBP1s expression.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, several reports have shown that GSK2606414 can act in a PERK-independent manner. GSK2606414 was demonstrated to be a potent inhibitor of RIPK1 kinase [50,51]. GSK2606414 was also able to inhibit KIT tyrosine kinase activity and enhance endocytosis and lysosomal degradation [52].…”
Section: Discussionmentioning
confidence: 99%